Designing A Project-Based Ecoliteration Learning Trajectory to Improve Students’ Ecological Intelligence - Fawziah Zahrawati B; Andi Aras; Syahrul; Jumaisa; Claver Nzobonimpa (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
The ecological crisis is one problem that has not yet found the right solution. This study intends to provide a solution to solve the ecological crisis by designing a project-based ecoliteracy learning trajectory to improve students’ ecological intelligence. This research is a design research which comprises three stages, namely: preliminary design, experimental design, and retrospective analysis. The research subjects were students from the Social Science Education Study Program, Faculty of Education, Institut Agama Islam Negeri Parepare. The data collection instruments used were questionnaires and observation guidelines. The study found that the trajectory of ecoliteracy learning goes through five learning stages, namely: identifying social ecological problems, planning the project design, preparing a schedule, observing social ecological problems to carry out the project, and present a social ecology project. An increase in ecological intelligence can occur because in this learning, students gain learning experiences that bring them closer to their surroundings so that they can grow their empathy for the environment. This learning combines textual and contextual learning. At the beginning, students are invited to gain a lot of knowledge by reading articles related to environmental problems. After that, they made observations in the surrounding environment to identify various environmental problems, their causes, affects, and solutions. The learning trajectories can be used by teachers in the learning process to improve students’ ecological intelligence. Keywords: Ecoliteracy, Ecological Intelligence, Project-Based Ecoliteration Learning Trajectory